IMPROVING STUDENT’S READING COMPREHENSION THROUGH MIND MAPPING TECHNIQUE AT A JUNIOR HIGH SCHOOL - Suryo Ganito; Andhi Dwi Nugroho; Theresia Laksmi Widyarini (STKIP PGRI Lubuklinggau, 2022)
The aim of this research is to improve students’ reading comprehension through the mind mapping technique in second-grade students of junior high school. In conducting the study, the researcher involved the English teacher, the school principal, and the students in the second grade of junior high school, especially in the VIII A class. This research conduct at SMP Taman Dewasa Ibu Pawiyatan Yogyakarta in Academic year 2021/2022 as the subject of researcher. The subjects of this research consisted of 20 students, male 11 and female 9. The research was conducted with descriptive design research. In conducting this design research, the researcher divided the design into two studies. The researcher collaborated with an English teacher in implementing the design. The data of this study were qualitative data. The qualitative data were from the observation checklist, interview transcript, diary notes, and documentation. While the qualitative table data were from post-test 1 and post-test 2, the result of students’ scores shows that the students’ average scores keep improving on every test. The percentage students score in study 1 (0,077%) and study 2 (0,085%). There were four students who have not passed the minimum mastery criterion (75) in study 1. In study 2 all students passed the minimum mastery criterion (75). Based on the quantitative data above, it can be seen that the students’ scores showed an improvement from the first to the last test. Furthermore, the qualitative data showed that all the learning activities gave contributions not only improved the students’ reading comprehension but also to the students’ interest, self-confidence, and motivation.